Pengaruh Lingkungan Kerja, Budaya Organisasi Dan Stres Kerja Terhadap Kinerja Karyawan Di Ptpn Xiii Afdeling I Kebun Tajati Kabupaten Paser - Annisa Rahmani Putri; Dr. H. Zainal Ilmi, SE, MBA; Dr. H. Irwansyah SE, MM (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2019)
ABSTRACTThis study aims to analyze factors affecting employee performance on PTPN XIII Section I Tajati Estate Paser Regency. The purpose of this study was to analyze the influence of work environment and organization culture toward job stress and employee performance on PTPN XIII Section I Tajati Estate Paser Regency.The data were analyzed by path analysis. The number of population 95 respondent. The collection of data by the method of questionnaire that is by giving data question to respondent which is closed with several alternative answer options.Results of this study concluded that work environment take effect positive and significant to job performance, organization culture take effect positive and significant to job performance, job stress take effect positive and not significant to job performance. The work environment, organization culture, and job stress influence simultaneously and significantly to job performance.